Volumetric modulated arc therapy treatment planning based on virtual monochromatic images for head and neck cancer: effect of the contrast‐enhanced agent on dose distribution. Issue 11 (21st October 2019) - Komiyama, Riho; Ohira, Shingo; Kanayama, Naoyuki; Karino, Tsukasa; Washio, Hayate; Ueda, Yoshihiro; Miyazaki, Masayoshi; Teshima, Teruki
Abstract: Virtual monochromatic images (VMIs) at a lower energy level can improve image quality but the computed tomography (CT) number of iodine contained in the contrast‐enhanced agent is dramatically increased. We assessed the effect of the use of contrast‐enhanced agent on the dose distributions in volumetric modulated arc therapy (VMAT) planning for head and neck cancer (HNC). Based on the VMIs at 40 keV (VMI40keV ), 60 keV(VMI60keV ), and 77 keV (VMI77keV ) of a tissue characterization phantom, lookup tables (LUTs) were created. VMAT plans were generated for 15 HNC patients based on contrast‐enhanced‐ (CE‐) VMIs at 40‐, 60‐, and 77 keV using the corresponding LUTs, and the doses were recalculated based on the noncontrast‐enhanced‐ (nCE‐) VMIs. For all structures, the difference in CT numbers owing to the contrast‐enhanced agent was prominent as the energy level of the VMI decreased, and the mean differences in CT number between CE‐ and nCE‐VMI was the largest for the clinical target volume (CTV) (125.3, 55.9, and 33.1 HU for VMI40keV, VMI60keV, and VMI77keV, respectively). The mean difference of the dosimetric parameters (D99%, D50%, D1%, Dmean, and D0.1cc ) for CTV and OARs was <1% in the treatment plans based on all VMIs. The maximum difference was observed for CTV in VMI40keV (2.4%), VMI60keV (1.9%), and VMI77keV (1.5%) plans. The effect of the contrast‐enhanced agent was larger in the VMAT plans based on the VMI at a lower energy level for HNC patients. This effect is not desirable in a treatment planning procedure.